A Psychological Pressure in Novels: “MENYUSU CELENG” - Setya Adi, Atanasius Raka; Tyas, Theresia Prias Hayu Purbaning (Universitas Mathla'ul Anwar Banten, 2024)
The content of the research aims to: 1) find out what factors or causes of psychological pressure are contained in the novel